Vehicle Service Locator Using GPS and Cloud Service on Android Platform - Yogarayan, Sumendra; Azman, Afizan; Wai Ko, Wai; Fatimah Abdul Razak, Siti; Jai Raman, Kirbana; Fikri Azli Abdullah, Mohd; Zainab Ibrahim, Siti; Sonai Muthu, Kalaiarasi; ., . (International Journal of Engineering and Technology, 2018)
Location-based services are becoming a part of everyday life especially with the development of mobile communication, which include navigation systems, emergency services, tour planning or even finding the most convenient restaurant around. They have been playing an important role in providing necessary services efficiently with the use of Global Positioning System (GPS). When it comes to vehicle servicing, the problems faced by the users still remain especially in case of emergency breakdown mostly in finding the nearest services available. Consequently, this gives the encouragement to come out with a solution, which would help users ease their process of solving such problems. Vehicle Service Locator (VSL) allows user to locate the nearest tow trucks available, towing services and nearest vehicle service centers according to userâ€™s location data obtained via GPS and provides directions based on the user's current location.Â Â